Hot Electron Tunneling in Pt/LaAlO3/SrTiO3Heterostructures for Enhanced Photodetection - Jeon, Jaeyoung; Eom, Kitae; Hong, Yunhwa; Eom, Chang Beom; Heo, Kwang; Lee, Hyungwoo (ACS Applied Materials and Interfaces, 2021)
LaAlO3/SrTiO3(LAO/STO) heterostructures, in which a highly mobile two-dimensional electron gas (2DEG) is formed, have great potential for optoelectronic applications. However, the inherently high density of the 2DEG hinders the observation of photo-excitation effects in oxide heterostructures. Herein, a strong photoresponse of the 2DEG in a Pt/LAO/STO heterostructure is achieved by adopting a vertical tunneling configuration. The tunneling of the 2DEG through an ultrathin LAO layer is significantly enhanced by UV light irradiation, showing a maximum photoresponsivity of ∼1.11 × 107%. The strong and reversible photoresponse is attributed to the thermionic emission of photoexcited hot electrons from the oxygen-deficient STO. Notably, the oxygen vacancy defects play a critical role in enhancing the tunneling photocurrent. Our systematic study on the hysteresis behavior and the light power dependency of the tunneling current consistently support the fact that the photoexcited hot electrons from the oxygen vacancies strongly contribute to the tunneling conduction under the UV light. This work offers valuable insights into a novel photodetection mechanism based on the 2DEG as well as into developing ultrathin optoelectronic devices based on the oxide heterostructures.
Keywords: 2D electron gas; LaAlO3/SrTiO3; Optoelectronic applications; Oxide heterostructures; Photo detection; Photoresponses; Tunneling device; Tunneling photocurrent; Two-dimensional electron gases (2DEG); Ultra-thin; 2D electron gas; hot electrons; LaAlO3/SrTiO3; oxygen vacancy; tunneling devices; tunneling photocurrent